Multi-methods Approach for Information Management Framework in Government Control in Human Resources - NEMA, DR. PRIYANKA (The journal of contemporary issues in business and government, 2021)
Knowledge management strategy roadmap consists of several stages to implement knowledge management in three government organizations that manage the process of managing the government's human capital. They are the Minister of State for State Organization Modernization (KEMENPAN & RB), National Civil Service Departments (BKN), and National Public Administration Institute (LAN). Generally speaking, this KM plan framework addresses three critical facets of human resource management by government that involve individuals, procedures, and technologies. This work explains the implementation of the KM strategy using multi-methods OCAI (Organizational Culture Assessment Instrument), evaluation of difference analysis and evaluation of risk analysis. Questionnaire and interviews are conducted to discover data relating to the government's human capital management KM strategy roadmap. The outcome of the roadmap for the KM plan was confirmed using expert judgement. Research finding the KM strategy roadmap for managing government human capital was described in three criteria and three phases. There are individuals (three phase), mechanism (three phase), technologies (two phase), and each phase has its own strategic plan of action.